G597 Psychometric evaluation of a novel self-harm assessment tool for use in acute paediatric settings. (May 2019) - Manning, JC; Carter, TM; Aubeeluck, A; Wood, DM; Coad, J; Bean, D
Abstract : We undertook psychometric evaluation of a novel 14-item clinical tool which assesses young people's immediate risk of self-harm and suicide when admitted to hospital in mental health crisis: the Children and Young People's Mental Health Self-harm Assessment Tool in Paediatric Healthcare Environments tool (SAPhE) Tool© . We aimed to establish the validity and reliability of this tool for young people and to further refine the tool for use in acute paediatric settings Young people presenting to three acute pediatric services in mental health crisis (cases) or with physical injury or illness (non-cases) were asked to complete the tool. Cases were also asked to complete the Columbia Suicide Severity Rating Scale: (C-SSRS) a standard measure of suicide risk. Factor analysis of Likert and dichotomous variables was undertaken along with assessment of face validity, inter-rater reliability, congruent validity and discriminant/divergent validity. A total of 163 young people with a mean age 14.3 years (SD 1.8) were recruited into the study of which 61 cases and 102 non-cases.) The 14-item CYP-MH SAT demonstrated high levels of inter-rater reliability, (Kappa=0.65, p<0.001), high levels of discriminant/divergent validity between cases and non-cases (Mann-Whitney U test U=1739, p<0.001) and a moderate positive correlation for congruent validity between the tool and the C-SSRS (rs, 0.438, p=0.001). Results of the factor analysis along with assessment of face validity resulted in refinement of the 14-item tool to an 8-item tool. This study demonstrated that the CYP-MH SAPhE Tool© had high levels of congruent and discriminant validity, was face valid and had high levels of inter-rater reliability. We have developed a clinically appropriate, psychometrically tested tool that assesses immediate risk of self-harm and suicide in acute paediatric settings.